Planning of Sharing Wall At Iup Boundaries As A Strategy For Coal Conservation And Compliance With Mining Regulations - Arie Kurniawan; Eddy Ibrahim; Taufik Toha; Rahmat Wahyudi Putra (International Journal of Science and Environment (IJSE), 2025)
Coal mining activities in adjacent Mining Business Permit (IUP) areas often face technical challenges at pit boundaries. Conventional double-wall pit designs generally lead to pit losses at border zones, increased overburden volume, and higher stripping ratios, resulting in reduced mining efficiency and suboptimal utilization of coal reserves. Meanwhile, Indonesian mining regulations—Law No. 3 of 2020 in conjunction with Law No. 4 of 2025, Government Regulation No. 96 of 2021, and Ministerial Decree of Energy and Mineral Resources (Kepmen ESDM) No. 1827 K/30/MEM/2018—emphasize the obligation to conserve mineral and coal resources through efficient and optimal mine planning. This study aims to evaluate the planning of sharing wall (joint boundary slope mining) at IUP boundaries as a strategy for coal conservation and regulatory compliance. The research methods include analyzing existing double-wall designs, developing an alternative sharing wall model, recalculating overburden volume, coal reserves, stripping ratio, and pit loss potential, and assessing technical results against conservation regulations. The case study was conducted at the boundary of PT Merapi Energy Coal’s IUP in Lahat Regency, South Sumatra. The analysis results show that implementing the sharing wall design results in a 70 million bcm deviation in overburden volume, an increase in stripping ratio from 5.39 to 5.94 bcm/ton, and an additional 11.8 million tons of recovered reserves compared to the double-wall design. This strategy supports resource conservation principles as stipulated in Kepmen ESDM No. 1827 K/30/MEM/2018, particularly regarding pit loss reduction and coal recovery optimization. Therefore, sharing wall planning not only enhances technical and economic efficiency but also strengthens compliance with national mining conservation regulations.